Characterisation of the bovine C-type lectin receptor Mincle and potential evidence for an endogenous ligand - Holder, Angela; Kolakowski, Jeannine; Rosentreter, Chloe; Knuepfer, Ellen; Jégouzo, Sabine A. F.; Rosenwasser, Oliver; Harris, Heather; Baumgaertel, Lotta; Gibson, Amanda; Werling, Dirk (Frontiers in Immunology, 2023)
Innate immune receptors that form complexes with secondary receptors, activating multiple signalling pathways, modulate cellular activation and play essential roles in regulating homeostasis and immunity. We have previously identified a variety of bovine C-type lectin-like receptors that possess similar functionality than their human orthologues. Mincle (CLEC4E), a heavily glycosylated monomer, is involved in the recognition of the mycobacterial component Cord factor (trehalose 6,6′-dimycolate). Here we characterise the bovine homologue of Mincle (boMincle), and demonstrate that the receptor is structurally and functionally similar to the human orthologue (huMincle), although there are some notable differences. In the absence of cross-reacting antibodies, boMincle-specific antibodies were created and used to demonstrate that, like the human receptor, boMincle is predominantly expressed by myeloid cells. BoMincle surface expression increases during the maturation of monocytes to macrophages. However, boMincle mRNA transcripts were also detected in granulocytes, B cells, and T cells. Finally, we show that boMincle binds to isolated bovine CD4+ T cells in a specific manner, indicating the potential to recognize endogenous ligands. This suggests that the receptor might also play a role in homeostasis in cattle